Spatial planning system. - Ibrahim, Rahinah; Hoseini, Ali Ghaffarian; Abdullah, Rusli (2008)
The present invention relates to a spatial planning system and method thereof. The spatial planning system is conveniently comprised of an information interface means for storing information of at least two nodes, a spatial organization component for arranging the stored information in order such that spatial relationship between two nodes is established is established based on the information; a spatial relationship analyzing components for connecting at least one pair of nodes which has functional relationship with each other with a link; a spatial displaying components for displaying the nodes and the link between the two linked nodes on a diagram; and a functional relationship maintainer component for maintaining the functional relationship of the at least one pair of linked nodes.